Unraveling the evolution, dynamics and time-scales of magmatic processes below the volcano, West-Java, Indonesia - Krimer, Daniel (2016)
Gede is the closest active stratovolcano to the capital of Indonesia, thus it is a potential hazard to millions of people around the volcano and in Jakarta. It is currently being monitored by various geophysical methods in a collaborative project between CVGHM and EOS. However, interpretation of new unrest is fraught with uncertainty unless its geological and petrological history is well understood. I present here a detailed petrochemical study to untangle Gede’s past history since about the last 45 kyr to present that sheds light on its magmatic evolution and reservoir dynamics, and the time-scales of these processes. A key finding is that Gede’s evolutionary path changed in the Holocene: the main magma dynamics has shifted from a deep mafic reservoir (about 24 km below its summit) to a shallow one (at about 4 km) made of silica-rich melts. Mingling and mixing of volatile-rich basaltic and crystal-rich rhyolitic magmas is one of the most important processes that lead to the main erupted compositions (andesites) and which also may lead to eruption. Three-dimensional numerical simulation of diffusion of chemically zoned minerals reveals that these shallow reservoir processes start probably only a month before eruption. These results should guide interpretations of monitoring signals and improve hazard mitigation efforts in a future unrest event.